A Bibliometric Analysis of Dams and Their Role in Socio Economic Development of a Region - Devraj Verma (Calibrating Urban Livability in the Global South, 2024)
Dams, as critical infrastructural assets, wield a profound influence on the development of regions by serving as backbone for water resource management, agricultural expansion, and power generation. Their strategic implementation contributes significantly to economic growth, environmental sustainability, and overall resilience within the affected regions. The aim of this paper is to conduct bibliometric analysis, through the Scopus database and explores the scholarly landscape of dams and their impact on regional development. Utilizing keyword analysis, the study provides a comprehensive overview of the existing literature, identifying trends, key themes, and research gaps in the field. The analysis delves into the multifaceted aspects of dam-related research, encompassing infrastructure development, water resource management, environmental impact, and socio-economic considerations. The insights derived from this bibliometric study not only contribute to understanding the current state of knowledge but also offer a roadmap for future research endeavours, guiding scholars and policymakers in advancing sustainable dam projects that foster regional development.